CAPITAL INFLOWS TO REGIONAL MOBILITY: SERVICE EXPORTS AS THE TRANSMISSION CHANNEL UNDER DIGITAL MODERATION IN ASEAN (2013–2022) - Gajendran, Saranya; Alfina, Alfina (Fakultas Dharma Duta UHN IGB Sugriwa Denpasar, 2025)
This study investigates how foreign direct investment (FDI) stimulates regional mobility through the service export channel, and whether digital access strengthens this transmission mechanism in ASEAN from 2013 to 2022. Despite the region’s progress in digital transformation, empirical evidence on how digitalization interacts with capital inflows to influence cross-border service performance and tourism mobility remains limited. Using panel data from ten ASEAN countries, this study applies Hayes’s PROCESS macro (Model 14) in SPSS to test a moderated mediation model, where service exports mediate the effect of FDI on intra-ASEAN visitor arrivals, and internet access moderates the link between service exports and visitor arrivals. The results confirm that FDI significantly increases service exports, which in turn enhance regional visitor mobility, supporting the mediating role of services. However, the moderating effect of internet access on this mediation pathway is not statistically significant. Although the indirect effect of FDI through services grows with higher digital access, the confidence intervals of the moderated mediation index include zero, indicating that the effect is not robust across digital levels. The findings imply that ASEAN’s service-led growth in tourism primarily depends on the intensity of investment rather than variations in digital penetration. Nonetheless, the consistent positive indirect effect highlights the central role of service exports as a policy-relevant bridge between capital inflows and people mobility. Enhancing service competitiveness and ensuring inclusive digital infrastructure remain essential for translating investment gains into sustainable regional tourism integration.